Hamstrings functional properties in athletes with high musculo-skeletal flexibility - Moltubakk, M. M.; Eriksrud, O.; Paulsen, G.; Seynnes, O. R.; Bojsen-Møller, J. (Scandinavian Journal of Medicine & Science in Sports, 2016)
The purpose of this study was to examine whether athletes with highly flexible hamstring muscle-tendon units display different passive and contractile mechanical properties compared with controls. Flexibility, passive, and active torque-angle properties were assessed in 21 female elite rhythmic gymnasts and 16 female age-matched athletes. Passive resistance to stretch was measured during knee extension with the hip fixed at 100° of flexion. Concentric isokinetic maximal voluntary knee flexion and extension torques were measured at 60°/s in the same position. Tests of flexibility and passive resistance to stretch indicated a greater flexibility in the gymnasts. Despite no differences between groups in knee flexion and extension peak torque, gymnasts reached knee flexion peak torque at more extended positions (longer muscle lengths) and displayed significantly different torque-angle relations. When active torque was corrected for passive resistance to stretch, differences increased, gymnasts producing more work, and maintaining = 70% of peak torque over a larger range of joint excursion. In conclusion, individuals with a higher flexibility of the hamstrings MTU present a different torque-angle profile, favoring the production of flexion torque toward extended knee positions, displaying larger functional range of motion and a higher mechanical work output during knee flexion.